Mastering data mining with Python : find patterns hidden in your data : learn how to create more powerful data mining applications with this comprehensive Python guide to advance data analytics techniques /: find patterns hidden in your data : learn how to create more powerful data mining applications with this comprehensive Python guide to advance data analytics techniques. (2016) - Squire, Megan
No abstract available